Partners in Mischief: Functional Networks of Heat Shock Proteins of Plasmodium falciparum and Their Influence on Parasite Virulence - Daniyan, Michael O.; Przyborski, Jude M.; Shonhai, Addmore (Biomolecules (Basel, Switzerland), 2019)
The survival of the human malaria parasite Plasmodium falciparum under the physiologically distinct environments associated with their development in the cold-blooded invertebrate mosquito vectors and the warm-blooded vertebrate human host requires a genome that caters to adaptability. To this end, a robust stress response system coupled to an efficient protein quality control system are essential features of the parasite. Heat shock proteins constitute the main molecular chaperone system of the cell, accounting for approximately two percent of the malaria genome. Some heat shock proteins of parasites constitute a large part (5%) of the ‘exportome’ (parasite proteins that are exported to the infected host erythrocyte) that modify the host cell, promoting its cyto-adherence. In light of their importance in protein folding and refolding, and thus the survival of the parasite, heat shock proteins of P. falciparum have been a major subject of study. Emerging evidence points to their role not only being cyto-protection of the parasite, as they are also implicated in regulating parasite virulence. In undertaking their roles, heat shock proteins operate in networks that involve not only partners of parasite origin, but also potentially functionally associate with human proteins to facilitate parasite survival and pathogenicity. This review seeks to highlight these interplays and their roles in parasite pathogenicity. We further discuss the prospects of targeting the parasite heat shock protein network towards the developments of alternative antimalarial chemotherapies.